2020
DOI: 10.1021/acs.energyfuels.9b04070
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis, Kinetics Modeling, and Reactor Model Development for Acetic Acid Hydrogenation Reaction over Bimetallic Pt–Sn Catalyst

Abstract: In present work, experiments for gas-phase acetic acid hydrogenation were conducted over SiO2–Al2O3 supported platinum–tin (Pt–Sn) catalysts. These experimental data were used to model the kinetics of acetic acid hydrogenation reaction based on two-site Langmuir–Hinshelwood–Hougen–Watson kinetic model. Kinetic parameters were determined, and excellent matches were found between the model calculated results and experimental data. In order to get a better insight into the effect of process parameters on conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For simplification, the formation of ethyl acetate as a by-product was neglected. This assumption is supported by the relatively low conversion level, as Rakshit et al (2020) showed that the degree of esterification, as a consecutive reaction to the main reaction, can be reduced at lower conversion levels.…”
Section: Acetic Acid Hydrogenation To Ethanolmentioning
confidence: 87%
See 2 more Smart Citations
“…For simplification, the formation of ethyl acetate as a by-product was neglected. This assumption is supported by the relatively low conversion level, as Rakshit et al (2020) showed that the degree of esterification, as a consecutive reaction to the main reaction, can be reduced at lower conversion levels.…”
Section: Acetic Acid Hydrogenation To Ethanolmentioning
confidence: 87%
“…Adapting the findings of Rakshit et al (2020), the acetic acid hydrogenation reactor was modelled as a stoichiometric reactor operated isothermally at 240 °C and 30 bar, with the conversion of the main reaction (Eq. 11) set to 75% as a conservative estimate.…”
Section: Acetic Acid Hydrogenation To Ethanolmentioning
confidence: 99%
See 1 more Smart Citation
“…In this substudy, two software packages (SuperPro Designer and ASPEN Plus Process Simulator) were used to develop large-scale simulation models for producing bioethanol from FW via biocatalytic and catalytic processes. The SuperPro Designer specialized for the modeling of the biocatalytic process was used for the simulation of AA and biogas production from food waste. , In addition, the ASPEN Plus Process Simulator specialized for modeling the catalytic conversion and separation was used for the simulation of AA extraction and conversion to produce bioethanol. , …”
Section: Methodsmentioning
confidence: 99%
“…Thermodynamics investigation involves studies on the whole reaction process in the steady state without considering the reaction kinetics aspects, e.g., the reaction rate and reaction time, from which one can know the degree of a reaction under different reaction parameters and the distribution of the products at equilibrium. , These thermodynamics insights can direct the catalysts’ design and reactor operation toward the target products. For the hydrogenation of alkynes and/or dienes in C 2 and C 3 streams, the simple thermodynamics analysis suggests that the formation of alkanes and green oil is thermodynamically favorable . However, due to the complexity of the hydrogenation processes in C 2 and C 3 streams, as schematically illustrated in Figure , more detailed and systematic thermodynamics investigations are of significance for the catalysts’ design and operation guidance, but are yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%